Strengthening the Digital Competence of Teachers at SMAN 2 Barru: Artificial Intelligence and Augmented Reality Literacy for Inclusive Entrepreneurship Innovation - Fakhri, M. Miftach; Andika Isma; Rosidah; Della Fadhilatunisa; Nurrahmah Agusnaya; Putri Nirmala (Panrannuangku Jurnal Pengabdian Masyarakat, 2025)
The digital competency strengthening program for teachers at SMAN 2 Barru focused on kecerdasan artifisial (KA) and augmented reality (AR) literacy to support inclusive entrepreneurship innovation. This activity was conducted to overcome limitations in the use of the latest technology among teachers, which previously hindered the development of research-based entrepreneurial products. The training methods used included introductory sessions, hands-on practice, and mentoring on the implementation of KA and AR technologies. The results of this program showed a significant improvement in the digital competency of the teachers, with the average pre-test score increasing from 73% to 80% after the training. In addition to improving technical skills, the training also strengthened teachers' confidence in utilizing KA and AR technology in the learning process and entrepreneurship development. However, limited infrastructure and external support remain challenges that need to be overcome to optimize the utilization of digital technology in schools. Recommendations are given to strengthen technology support and ongoing mentoring programs to improve the sustainability of technology implementation in learning and entrepreneurship activities.